Überprüfung internationaler wasserwirtschaftlicher Übereinkommen im Hinblick auf die Implementierung der Wasserrahmenrichtlinie ; Forschungsbericht 20121213 - Deutschland / Umweltbundesamt (Umweltbundesamt, 2002)
Community-european law, environmental law, water law, transboundary waters, water protection, EC-Waterframework Directive, International River Commissions
Zsfassung in engl. Sprache u.d.T.: Examination of international water management agreements with regard to the implementation of the Water Frameword Directive